2021
DOI: 10.1177/1069031x211028589
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Middle-Class Consumers in Africa: A Cross-Country City-Based Investigation Outlining Implications for International Marketers

Abstract: This article reports on a cross-country city-based investigation that profiled the middle class in Africa and distinguished discrete segments that demonstrate the importance of heterogeneity when studying the middle class. The authors identified three distinct middle-class segments by administering both qualitative and quantitative questionnaires across ten cities. Consumer-behaviour-related factors, like lifestyle and purchasing, were explored to answer calls to provide more marketing insight into the African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…As chronic diseases such as type 2 diabetes ( Vorster, Kruger, & Margetts, 2011 ), cardiovascular disease ( Keates, Mocumbi, Ntsekhe, Sliwa, & Stewart, 2017 ), cancer ( Bahnassy, Abdellateif, & Zekri, 2020 ), and kidney disease ( Kaze, Ilori, Jaar, & Echouffo-Tcheugui, 2018 ) continue to skyrocket in Africa, there is a growing need to promote healthy sustainable eating patterns. In the last 15 years, the rising middle class in East Africa has bought more disposable income to families that once experienced poverty ( Chikweche, Lappeman, & Egan, 2021 ). How this new middle-class values hierarchy and symbolism of status foods will be critical to achieving healthy diets and better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As chronic diseases such as type 2 diabetes ( Vorster, Kruger, & Margetts, 2011 ), cardiovascular disease ( Keates, Mocumbi, Ntsekhe, Sliwa, & Stewart, 2017 ), cancer ( Bahnassy, Abdellateif, & Zekri, 2020 ), and kidney disease ( Kaze, Ilori, Jaar, & Echouffo-Tcheugui, 2018 ) continue to skyrocket in Africa, there is a growing need to promote healthy sustainable eating patterns. In the last 15 years, the rising middle class in East Africa has bought more disposable income to families that once experienced poverty ( Chikweche, Lappeman, & Egan, 2021 ). How this new middle-class values hierarchy and symbolism of status foods will be critical to achieving healthy diets and better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Digital technologies are reducing information and time asymmetries between customers and sellers in significant ways (Kannan and Li, 2017) resulting in consumers having more information to consider moving through the different stages in the buying process; awareness, familiarity, consideration, evaluation and purchase. Consumers are acquiring information concerning goods or services in a variety of ways, Chikweche et al (2021) concluded that early global consumers in Africa are more likely to be influenced by the media whilst middle class African consumers are influenced more by peers. Highly valuable information concerning such products or services are available online and lead to repeat purchases in brand communities (Zaglia, 2013;Hua et al, 2015), focused information available on search engines and other customers' reviews that are on retailers' sites or third-party forums not controlled by the seller (Court et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increased consumer incomes and improved job opportunities available following market liberalisation in the emerging markets have contributed to the creation of a group of young, urban consumers often called the "new middle class" (NMC) (Cavusgil et al, 2018;Lange & Meier, 2009;Kravets & Sandikci, 2014). These consumers are known to be pursuing more material consumption and increasingly consumerist lifestyles (Brosius, 2010;Chandrasekara, Wijetunga, & Jayakody, 2023;Chikweche, Lappeman, & Egan, 2021, 2022Lange & Meier, 2009;Pinches, 1999). Consumers are buying more cars, home appliances, improving climate control in their homes through air-conditioning, and have a growing interest in overseas sightseeing (de Koning et al, 2015;de Koning, Ta, Crul, Wever, & Brezet, 2016;Hansen, 2017aHansen, , 2017bLange & Meier, 2009;Never & Albert, 2021;Suyanto, Sugihartati, Hidayat, & Subiakto, 2019).…”
Section: Problem Identificationmentioning
confidence: 99%
“…Currently, most studies on middle class consumers in emerging markets across business disciplines seek to identify and define middle class membership and measure middle class consumption (e.g., Belbağ, Üner, Cavusgil, & Cavusgil, 2019;Cavusgil et al, 2018;Chikweche & Fletcher, 2014;Chikweche et al, 2021Chikweche et al, , 2022Lappeman du Plessis, Ho, Louw, & Egan, 2021;Song, Cavusgil, Li, & Luo, 2016). Additionally, existing research acknowledges the significant value that NMC consumers place on material consumption as a tool for achieving social distinction (Brosius, 2010;Javalgi & Grossman, 2016;Mathur, 2010;Suyanto et al, 2019;Uner & Gungordu, 2016;Ustuner & Holt, 2010).…”
Section: Motivations and Opportunity For The Studymentioning
confidence: 99%
See 1 more Smart Citation